Design and evaluation of medium speed geared direct grid connected wind generator drive train with specific focus on slip permanent magnet coupling - Van Wyk, Petrus Johannes Jacobus (Stellenbosch : Stellenbosch University, 2015)
Thesis (MEng)--Stellenbosch University, 2015.